Aberrant nuclear factor-kappa B activity in acute myeloid Leukemia: from molecular pathogenesis to therapeutic target - Zhou, Jianbiao; Ching, Ying Qing; Chng, Wee-Joo (Oncotarget, 2015)
The overall survival of patients with acute myeloid leukemia (AML) has not been improved significantly over the last decade. Molecularly targeted agents hold promise to change the therapeutic landscape in AML. The nuclear factor kappa B (NF-κB) controls a plethora of biological process through switching on and off its long list of target genes. In AML, constitutive NF-κB has been detected in 40% of cases and its aberrant activity enable leukemia cells to evade apoptosis and stimulate proliferation. These facts suggest that NF-κB signaling pathway plays a fundamental role in the development of AML and it represents an attractive target for the intervention of AML. This review summarizes our current knowledge of NF-κB signaling transduction including canonical and non-canonical NF-κB pathways. Then we specifically highlight what factors contribute to the aberrant activation of NF-κB activity in AML, followed by an overview of 8 important clinical trials of the first FDA approved proteasome inhibitor, Bortezomib (Velcade), which is a NF-κB inhibitor too, in combination with other therapeutic agents in patients with AML. Finally, this review discusses the future directions of NF-κB inhibitor in treatment of AML, especially in targeting leukemia stem cells (LSCs).